Measurement of Social Factors Affecting Self-Declaration Health (Case study, 6 and 16 districts of Tehran): Social Factors Affecting Self-Declaration Health - Abbasi, Mahmoud; Yahak, Sajjad; Keshavarz dizjini, Sara (Bioethics and Health Law Journal (BHL), 2022)
Background and Aim: Health has other dimensions in addition to its physical dimension. Health is a result of socio-economic and cultural life conditions and qualities and has close relation with economic stability, environment, neighborhood situation, health care, social, cultural context, education level, and knowledge. In this study, we examined the possible effect of social factors on diverse health levels. The aim is to investigate the relationship between health and independent variables such as lifestyle, health literacy, and socio-economic status. Methods: Data was gathered with a survey method and 256 sample sizes of 3 and 16 municipal districts of Tehran using structured and semi-structured questionnaires. Validity was examined by content validity, and reliability was examined by Cronbach’s alpha. Data were analyzed with SPSS software. Ethical Considerations: In this study, verbal informed consent of participants was obtained followed by an explanation about the purpose of the study, anonymity, and confidentiality of patients’ information. Results: Results indicate that the general condition of health has a significant relation with all independent variables (lifestyle, health literacy, and socioeconomic status). In examining the relation of two-dimension of physical and mental health with independent variables; physical health has a significant relation with gender, healthy lifestyle, health literacy, social support, and socioeconomic status; and mental health has a significant relationship with a healthy lifestyle, health literacy, social capital. Conclusion: Analysis of stepwise regression shows that independent variables explain 9 percent of health variation so that health literacy has more effect and with adding demographical variables increases to 17 percent. Corresponding Author: Sajjad Yahak; Email: syyahaks@gmail.com; ORCID: https://orcid.org/0000-0003-0037-7935 Please cite this article as: Abbasi M, Yahak S, Keshavarz dizjini S. Measurement of Social Factors Affecting Self-Declaration Health (Case study, 6 and 16 districts of Tehran). Bioeth Health Law J. 2022; 2(1): 1-10 (e4). http://doi.org/10.22037/bhl.v2i1.38952